Metallic cables and other passive components test methods. Electromagnetic compatibility (EMC). Extension of the frequency range to higher frequencies for transfer impedance and to lower frequencies for screening attenuation measurements using the triaxial set-up Part 4-16, (11th October 2021) - British Standards Institution,
No abstract available